RADIATION BUDGET OBSERVATION AT ASUKA CAMP, ANTARCTICA, IN 1988 : CLOUD RADIATIVE FORCING - アオキ, テルオ; ヤマノウチ, タカシ; AOKI, Teruo; YAMANOUCHI, Takashi (National Institute of Polar Research, 1991)
P(論文) Upward and downward radiation on the snow surface were observed at Asuka Camp (72°31'S, 24°08'E, 930m a. s. l.), Antarctica, from January to December 1988. We have studied the effect of clouds on the surface radiation budget and have found that the long wave (LW) greenhouse effect of clouds exceeded the short wave (SW) albedo effect of clouds, so that net (SW+LW) cloud-radiative forcing on the snow surface was heating. The heating mechanism is explained as follows : (1) Short wave : The downward short wave radiation on a cloudy day is only slightly less than on a clear day due to the multi-reflection effect between cloud and snow surface. On the other hand, there is no significant difference of snow albedo between clear and cloudy days. Therefore, the net radiation on a cloudy day does not largely decrease from that on a clear day. That is, SW cloud-radiative forcing is only weak cooling. (2) Long wave : The downward long wave radiation on a cloudy day increases from that on a clear day, because of additional emission from the cloud. In addition, since the air temperature is very low and the water vapor contained in the atmosphere is very little on a clear day, the equivalent black body temperature of the downward radiation is very low so that the difference of downward radiation between clear and cloudy days is large. On the other hand, the difference of upward radiation between clear and cloudy days is not so large. Therefore the net longwave radiation on a cloudy day largely increases from that on a clear day. That is, LW cloud-radiative forcing is strong heating. departmental bulletin paper